THE ROLE OF DISCRIMINATION LEARNING IN AGE DIFFERENCES IN RISK TAKING. (11th November 2018) - Chong, A; Lam, P H; Karnilowicz, H R; Mauss, I B; Löckenhoff, C E
Abstract: Older adults (OAs) are generally more risk averse than younger adults (YAs) on the Balloon Analogue Risk Task (BART), but OAs are also less successful in avoiding explosions than YAs. The present study examines whether these age differences are primarily driven by (1) risk-taking tendencies, or (2) both risk taking and learning. We hypothesized that OAs would perform less well than YAs, particularly with regard to discrimination between balloon capacities, and that this age difference would increase with experience. 49 younger females (mean age = 29.8, SD = 5.4) and 37 older females (mean age = 62.4, SD = 5.4) completed the BART with high- and low-capacity balloons, presented in a randomized order. OAs pumped less and gained fewer points than did YAs. Supporting our hypothesis, OAs, relative to YAs, discriminated less between balloon capacities. Exploratory analyses examining the role of physiological responses in discrimination learning will be discussed.